A Qualitative Analysis into the Strategic Priorities of the Indonesian Bank Industry - Ridloah, Siti (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2016)
This research paper investigates present day strategic priorities employed by large (foreign exchange) banks in Indonesian banking industry. The research used idea networking of the mission statements of banks as the means to identifying a handful of priorities. The population comprised commercial banks in Indonesia. Foreign exchange banks in Indonesia were chosen as a sample of this study .The study was conducted in 2014. The research method utilized in this study is qualitative clustering through idea networking. In this method, the idea statements were extracted and linked to each other to produce diagrams resulting in clusters of statements that were generalized into priorities. The finding from this study is that Indonesian banks have six main priorities of service excellence, prudent corporate governance, innovative, customer segmentation focus, professionalism and social responsibility. This, undoubtedly, provides some insight into the potential threats to the Indonesian bank industry as well as an agenda for change.